Unpacking the critical elements for solving the complex issue of sustainable lake management: Case studies from Japan - Yukako Inamura; Pankaj Kumar; Naoko Hirayama (World Development Sustainability)
Although water is a vital finite resource for sustaining life, it is under constant pressure from anthropogenic activities. Among the different types of surface water, lakes are particularly difficult to restore once water quality deteriorates due to their hydrological cycles and complex dynamics. This study compares policy implementation and its relationship to water quality improvement through spatio-temporal variation for two lakes in Japan: Lake Biwa and Lake Teganuma. We divided the analysis time frame into three periods to assess how the timing of policy implementation has affected the water quality and ecosystem services. Lake Biwa is an iconic and vital water resource in the region, and its conservation has been led by citizens and strong leadership from the governor since the 1960s. On the other hand, efforts to conserve the environment of Lake Teganuma began in the 1970s, and legislation played an important role in initiating and implementing the governance framework. The comparison of these two cases shows that while the efforts of subnational government and citizen are as powerful as legislation in protecting the lake environment, special legislation can guide subnational governments in establishing the necessary governance framework that fits local conditions and goals. Achieving regional sustainability in a human-environment system requires policy planning that goes beyond silo thinking, and this study clearly shows that cooperation between multilevel governments and relevant stakeholders, including citizens, is essential. The findings provide policy-relevant practical lessons in the quest for sustainable lake management.